Antibody-mediated delivery of CRISPR-Cas9 ribonucleoproteins in human cells. (7th November 2022) - Ubiparipovic, Stephanie; Christ, Daniel; Rouet, Romain
Abstract: The CRISPR genome editing technology holds great clinical potential for the treatment of monogenetic disorders such as sickle cell disease. The therapeutic in vivo application of the technology relies on targeted delivery methods of the Cas9 and gRNA complex to specific cells or tissues. However, such methods are currently limited to direct organ delivery, preventing clinical application. Here, we show that monoclonal antibodies can be employed to deliver the Cas9/gRNA complex directly into human cells via cell-surface receptors. Using the SpyCatcher/SpyTag system, we conjugated the Fab fragment of the therapeutic antibodies Trastuzumab and Pertuzumab directly to the Cas9 enzyme and observed HER2-specific uptake of the ribonucleoprotein in a human HER2 expressing cell line. Following cellular uptake in the presence of an endosomolytic peptide, modest gene editing was also observed. This finding provides a blueprint for the targeted delivery of the CRISPR technology into specific cells using monoclonal antibodies. Graphical abstract: